The Roman emperor and his court c. 30 BC-c. AD 300 - Kelly, Benjamin, (Cambridge University Press, 2022)
"At the centre of the Roman empire stood the emperor and the court surrounding him. The systematic investigation of this court in its own right, however, has been a relatively late development in the field of Roman history, and previous studies have focused on narrowly defined aspects or on particular periods of Roman history. This book makes a major contribution to understanding the history of the Roman imperial court. The first volume presents nineteen original essays covering all the major dimensions of the court from the age of Augustus to the threshold of Late Antiquity. The second volume is a collection of the ancient sources that are central to studying that court. The collection includes: translations of literary sources, inscriptions, and papyri; plans and computer visualizations of archaeological remains; and photographs of archaeological sites and artworks depicting the emperor and his court"--